Coalizer: A coalition tool combining office and policy motivations of political parties. Issue 3 (3rd July 2021) - Graichen, Robin; Linhart, Eric; Schuster, Christopher; Heller, Udo; Müller, Andreas
ABSTRACT: While prior work on coalition theories focuses either solely on office or on policy motivations of parties, more elaborate theories combine both types of motivation. Said combination makes them much more appropriate for explaining coalition formation but also more complex. One possibility to make these models broadly applicable are coalition tools. Since existing tools do not incorporate advances from such theories, we present a new coalition tool called Coalizer which takes both office and policy motivations into account and reflects the state of coalition theory. Among others, Coalizer includes features like the computation of policy utility values basing on party positions (supporting different estimation modes), the combination of office and policy utility values, and the indication of utility maximizing strategies for parties. In this paper, we present our coalition tool and illustrate its functionality with the example of the German federal elections in 2017. Coalizer is available online at www.mytuc.org/mcbz